2017
DOI: 10.1111/jch.12967
|View full text |Cite
|
Sign up to set email alerts
|

A study of the VaSera arterial stiffness device in US patients

Abstract: The Cardio-Ankle Vascular Index (CAVI) represents a promising index of arterial stiffness. However, neither the CAVI measure nor its measurement device, the VaSera, have undergone general testing in a North American clinical setting. To begin the process of collecting normal values in the USA, we studied 20 male and 28 female volunteers without reported cardiovascular or renal disease and no history of smoking. Their CAVIs, Ankle-Brachial Indices (ABIs), and 4-limb blood pressures were measured in 3 positions:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
0
7
0
2
Order By: Relevance
“…BP measurements obtained at the lower extremities, including ankle BP, have been well studied [3,5,6,25,26,28,29]. Wilkes et al [6] reported that the ankle is a suitable alternative site for BP measurement only when the arm is not available, because ankle BP measurements tend to be higher than brachial ones [3,6,25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BP measurements obtained at the lower extremities, including ankle BP, have been well studied [3,5,6,25,26,28,29]. Wilkes et al [6] reported that the ankle is a suitable alternative site for BP measurement only when the arm is not available, because ankle BP measurements tend to be higher than brachial ones [3,6,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Proposed reasons for the higher leg BP readings include greater resistance of distal vessels, ineffective compression by the cuff on the posterior tibial artery and poor detection of the oscillations [26]. In addition, ankle BP measurements may be affected by positions, such as the lithotomy and reverse Trendelenburg positions [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The VaSera device uses the four-cuff oscillometric system with the ECG recording and an amorphous pulse wave sensor placed on the carotid and the femoral arteries. The device estimates several parameters correlated with arterial stiffness, especially the PWV and CAVI index [13,14,15,16,17]. These devices are relatively expensive and requires trained technician for accurate results, which is disadvantageous for implementing in the wider general internal, and preventative offices.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, the above-mentioned phenomena will likely occur when other indices are measured using devices, such as CAVI, VaSera, 41 45 and other similar devices in other countries. 46 50 The contents of this article would be useful in interpreting the results and pitfalls of the four-limb BP/ABI/PWV measurements.…”
Section: Discussionmentioning
confidence: 99%